GAMBARAN KETERAMPILAN MENGELOLA KELAS GURU PAUD DI KECAMATAN KUBU BABUSSALAM KABUPATEN ROKAN HILIR - Desiyanti, Desiyanti; Chairilsyah, Daviq; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine the skills associated with the creation and maintenance of optimal learning conditions. Population and sample in this research that is all teacher of Kindergarten in District KubuBabussalamRokanHilir Regency as many as 55 people. The data collection technique is using observation. Data analysis techniques using the formula percentage. The skills of managing the early childhood teachers' classes in KubuBabussalam sub-district of RokanHiir Regency are categorized as sufficient. This means that PAUD teachers in KubuBabussalam Sub-district of RokanHilir Regency are sufficient in performing their duties as educators and able to run their management skills adequately. Skill indicators related to the creation and maintenance of optimal learning conditions are in either category. This means that early childhood teachers in KubuBabussalam sub-district RokanHilir district have been able to achieve the goals of classroom management skills. This is evidenced by showing responsiveness, paying attention, focusing the group, providing clear clues, rebuking, and reinforcing. Skill indicators related to optimal return of learning conditions, are in enough categories. This means that PAUD teachers in KubuBabussalam sub-district of RokanHilir district are quite able to modify children's behavior, using group problem-solving approach and can find and solve the problematic behavior.Keywords: Manage Classroom Skills